Σ+ production in pp collisions at √s=13 TeV - Abualrob, I. J.; Acharya, S.; Rinella, G. Aglieri; Aglietta, L.; Agnello, M.; Agrawal, N.; Ahammed, Z.; Ahmad, S.; Ahuja, I.; Akbar, Z.; Akindinov, A.; Akishina, V.; et al. (SPRINGER, 2026)
The measurement of Sigma(+) production in pp collisions at root s = 13 TeV is presented. The measurement is performed at midrapidity in both minimum-bias and high-multiplicity pp collisions at root s = 13 TeV. The Sigma(+) is reconstructed via its weak-decay topology in the decay channel Sigma(+) -> p + pi(0) with pi(0) -> gamma + gamma. In a novel approach, the neutral pion is reconstructed by combining photons that convert in the detector material with photons measured in the calorimeters. The transverse-momentum (p(T)) distributions of the Sigma(+) and its rapidity densities dN/dy in both event classes are reported. The p(T) spectrum in minimum-bias collisions is compared to QCD-inspired event generators. The ratio of Sigma(+) to previously measured Lambda baryons is in good agreement with calculations from the Statistical Hadronization Model. The high efficiency and purity of the novel reconstruction method for Sigma(+) presented here will enable future studies of the interaction of Sigma(+) with protons in the context of femtoscopic measurements, which could be crucial for understanding the equation of state of neutron stars.
Keywords: MULTIPLICITY DEPENDENCE; CHARGED-PARTICLES; HADRON-PRODUCTION; STRANGE; QCD; Physics